2018
DOI: 10.1016/j.envpol.2018.06.042
|View full text |Cite
|
Sign up to set email alerts
|

The interactions of fullerene C60 and Benzo(α)pyrene influence their bioavailability and toxicity to zebrafish embryos

Abstract: This study aimed to assess the toxicological consequences related to the interaction of fullerene nanoparticles (C) and Benzo(α)pyrene (B(α)P) on zebrafish embryos, which were exposed to C and B(α)P alone and to C doped with B(α)P. The uptake of pollutants into their tissues and intra-cellular localization were investigated by immunofluorescence and electron microscopy. A set of biomarkers of genotoxicity and oxidative stress, as well as functional proteomics analysis were applied to assess the toxic effects d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…As already observed in [72], mixture did not increase the formation of DNA strand breaks in the In our study, the antagonistic effect observed in the co-exposure treatment at the highest concentration may be caused by a reduction in ROS generation, or more effective scavenging of ROS by C60, when C60 and BaP are present together in close association, as previously described by [9,72].…”
Section: Dna Damagesupporting
confidence: 85%
See 1 more Smart Citation
“…As already observed in [72], mixture did not increase the formation of DNA strand breaks in the In our study, the antagonistic effect observed in the co-exposure treatment at the highest concentration may be caused by a reduction in ROS generation, or more effective scavenging of ROS by C60, when C60 and BaP are present together in close association, as previously described by [9,72].…”
Section: Dna Damagesupporting
confidence: 85%
“…The toxicity associated with C60 is controversial and largely unclear [6]. The ability of C60 to both generate and quench reactive oxygen species (ROS) has recently been recognised as a particularly important property in the interaction of fullerenes with biological systems [7], with many aquatic studies demonstrating that fullerenes are capable of eliciting toxicity via oxidative stress [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…While single exposure studies are more common, bivalve species have already been used as biological models in proteomics to assess the effects of complex mixtures [22,76,77]. However, proteomics analyses on combined exposure with carbon nanomaterials in aquatic organisms are still very scarce [9].…”
Section: Resultsmentioning
confidence: 99%
“…The toxicity associated with C 60 is controversial and largely unclear [6]. The ability of C 60 to both generate and quench reactive oxygen species (ROS) has recently been recognised as a particularly important property in the interaction of fullerenes with biological systems [7], with many aquatic studies demonstrating that fullerenes are capable of eliciting toxicity via oxidative stress [8,9,10]. Numerous studies have investigated the beneficial and toxicological effects of fullerenes [11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Multiwalled carbon nanotubes Embryo [130] Single wall carbon nanotubes Embryo [131] Graphene quantum dot Embryo [132] Carbon dots Embryo [133] Pristine graphene Embryo [134] Graphene oxide Larvae [135] Fullerene Embryo and adult [136,137] Polymer nanoparticles Chitosan Embryo [138] Hydroxy apatite Embryo [139] Poly (lactic-co-glycolic acid) (PLGA) Life stages and adult [140] Anionic and cationic polyamidoamine (PAMAM) and poly (propylene imine) (PPI) Embryo [141] Bismuth-asparagine Embryo [142] Redox polymer Embryo [143] Iron chelator starch-deferoxamine Embryo [144] Nanocomposites Graphene oxide-titanium dioxide Embryo and larvae [145] Chitosan-zinc oxide Early stages of zebrafish [146] Starch-magnetite Adult [147] Titanium dioxide-multiwalled carbon nanotube Embryo [148] Gold-gadolinium doped-carbon quantum dot Embryo [149] Titanium dioxide-chondroitin-4-sulfate Embryo and life stages [150]…”
Section: Metal Nanoparticlesmentioning
confidence: 99%